2017
DOI: 10.1038/nature21677
|View full text |Cite
|
Sign up to set email alerts
|

Star formation inside a galactic outflow

Abstract: Recent observations have revealed massive galactic molecular outflows 1-3 that may have physical conditions (high gas densities 4-6 ) required to form stars. Indeed, several recent models predict that such massive galactic outflows may ignite star formation within the outflow itself 7-11 . This star-formation mode, in which stars form with high radial velocities, could contribute to the morphological evolution of galaxies 12 , to the evolution in size and velocity dispersion of the spheroidal component of gala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
218
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(234 citation statements)
references
References 45 publications
16
218
0
Order By: Relevance
“…Radio observations reveal large molecular outflows with velocities of 100 km s −1 up to a few times 1000 km s −1 (Aalto et al 2012;Cicone et al 2014). Recently, Maiolino et al (2017) report star formation inside a galactic outflow, another strong indication for the presence of an outflow of cold gas. In Mrk231, the closest and best-studied quasar, we observe velocities of ∼ 1000 km s −1 and mass outflow rates of the order ∼ 1000 M yr −1 (Feruglio et al 2010;Rupke & Veilleux 2011;Sturm et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Radio observations reveal large molecular outflows with velocities of 100 km s −1 up to a few times 1000 km s −1 (Aalto et al 2012;Cicone et al 2014). Recently, Maiolino et al (2017) report star formation inside a galactic outflow, another strong indication for the presence of an outflow of cold gas. In Mrk231, the closest and best-studied quasar, we observe velocities of ∼ 1000 km s −1 and mass outflow rates of the order ∼ 1000 M yr −1 (Feruglio et al 2010;Rupke & Veilleux 2011;Sturm et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, AGN outflows may trigger star formation by compressing the gas within the process known as positive feedback (see e.g. Maiolino et al 2017). Ultrafast outflows (UFOs, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In all the five diagnostic diagrams (Figure 2 in Maiolino et al, 2017) we have found that the line ratios for the broad outflowing component are typical of HII star-forming regions. Furthermore, on the one hand coronal lines associated with AGN excitation (e.g., S IXλ1.252 and Al IXλ2.045µm) are absent in the near IR spectra.…”
Section: Star Formation Inside the Outflow Of Iras F23128-5919mentioning
confidence: 95%
“…The southern galaxy is characterized by a prominent outflow studied by various authors through emission and absorption lines (Piqueras López et al, 2012;Bellocchi et al, 2013;Arribas et al, 2014;Cazzoli et al, 2016). In order to investigate if the multiphase outflow is able to undergo vigorous SF as expected in case of positive feedback (section 1) we have combined archival optical MUSE/VLT data with new X-shooter/VLT observations (Maiolino et al, 2017).…”
Section: Star Formation Inside the Outflow Of Iras F23128-5919mentioning
confidence: 99%